2004
DOI: 10.1152/japplphysiol.00855.2003
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-induced activation of muscle afferents modulates bioassayable growth hormone release

Abstract: The effects of tendon vibration on bioassayable growth hormone (BGH) secretion from the pituitary gland were investigated in anesthetized adult male rats. The tendons from predominantly fast-twitch ankle extensor muscles (gastrocnemius and plantaris) or a predominantly slow-twitch ankle extensor (soleus) were vibrated by using a paradigm that selectively activates group Ia afferent fibers from muscle spindles. The lower hindlimb was secured with the muscles near physiological length, and the tendons were vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…Ten to 15 min of tendon direct vibration were shown to induce an increase in bioassayable growth hormone (BGH) releases in rats (Gosselink et al, 2004) as in humans (McCall et al, 2000). Those studies are in favor of a muscle afferent-pituitary axis that modulates the release of BGH from primary endings of muscle spindles.…”
Section: Discussionmentioning
confidence: 99%
“…Ten to 15 min of tendon direct vibration were shown to induce an increase in bioassayable growth hormone (BGH) releases in rats (Gosselink et al, 2004) as in humans (McCall et al, 2000). Those studies are in favor of a muscle afferent-pituitary axis that modulates the release of BGH from primary endings of muscle spindles.…”
Section: Discussionmentioning
confidence: 99%
“…These existing studies have collectively demonstrated, (1) a dichotomy exists in terms of the relative ''responsiveness" of iGH vs. bioGH [9] and that (2) bioGH is influenced by afferent neuromuscular activity [15,16]. For example, Kraemer et al [9] recently demonstrated that acute resistance exercise elicits an increase in iGH, but not bioGH, while chronic resistance exercise training elicits an increase in bioGH, but not iGH.…”
Section: Discussionmentioning
confidence: 99%
“…13,20 Bosco et al 13 suggested that the activation of hypothalamic autonomic and neurosecretory centers by collaterals of the central motor command in combination with positive feedback influences from proprio-and metaboreceptors in muscles. Therefore, available data on the effect of WBV on the secretion of cortisol are consistent in human and animal studies in contrast to data on the release of GH that partly provide evidence that mechanical vibration-induced activation of muscle afferents is capable of producing a hormonal response primarily modulating the release of GH in both rats 16 and man. 13,21 The finding that WBV induces an increase of serotonin (5-HT) in the brain in combination with decreased plasma cortisol levels was also previously reported by Ariizumi and Okada 15 in the rat.…”
Section: Discussionmentioning
confidence: 80%
“…8 The effects of vibration therapy on bone formation were also reported for low acceleration (low magnitude mechanical) signals that do not stimulate the muscular spinal reflex arc, in contrast to side-alternating WBV. 15,16 The studies conducted in humans produced differing results that also deviate from results reported in intensive exercises. The effect of vibration on hormonal secretion was explored in recently published studies focused on men 9 -14 and rodents.…”
mentioning
confidence: 99%